Physical interactions between DinI and RecA nucleoprotein filament for the regulation of SOS mutagenesis - Yasuda, Takeshi (Oxford University Press, 2001)
The Escherichia coli dinI gene is one of the LexA-regulated genes, which are induced upon DNA damage. Its overexpression conferred severe UV sensitivity on wild-type cells and resulted in the inhibition of LexA and UmuD processing, reactions that are normally dependent on activated RecA in a complex with single-stranded (ss)DNA. Here, we study the mechanism by which DinI inhibits the activities of RecA. While DinI neither binds to ssDNA nor prevents the formation of RecA nucleoprotein filament, it binds to active RecA filament, thereby inhibiting its coprotease activity but not the ATPase activity. Furthermore, even under in vitro conditions where UmuD cleavage dependent on RecA–ssDNA–adeno sine-5′-(3-thiotriphosphate) is blocked in the presence of DinI, LexA is cleaved normally. This result, taken together with electron microscopy observations and linear dichroism measurements, indicates that the ternary complex remains intact in the presence of DinI, and that the affinity to the RecA filament decreases in the order LexA, DinI and UmuD. DinI is thus suited to modulating UmuD processing so as to limit SOS mutagenesis.